What's new in treatment of pancreatic cancer: a patent review (2010–2017). (2nd November 2017) - Ramos, Maria C.; Boulaiz, Houria; Griñan-Lison, Carmen; Marchal, Juan Antonio; Vicente, Francisca
ABSTRACT: Introduction : Pancreatic cancer (PC) is one of the most lethal cancers, with a median overall survival of less than 1 year and a 5-year survival of 5%. The poor survival rate is likely due to lack of early diagnosis, fast disease course, high metastasis rate and disappointing treatment outcome. Therefore, at this stage, any new method that provides a treatment against PC without the undesirable side effects of chemotherapy and radiation is urgently needed. Areas covered : This review summarizes the latest advances in the treatment of PC through the patents published from 2010 to 2017. The patents reviewed include both new combinations of existing drugs and novel structures. New targets are proposed for developing new drugs. Expert opinion : The patents reviewed entail different approaches which, on the one hand, improve the administration of existing drugs and therapies and, on the other, develop new drugs to act on novel targets. However, most of the new methods are in the first stage of development and need to be tested in vivo, in pre-clinical approaches and in clinical trials. Therefore, further assays will help confirm the activity, mechanisms of action, drug-drug interactions and other aspects that make a compound a good antitumoral agent.